Do energy consumption and economic growth lead to environmental degradation? Evidence from Asian economies - Lamia Jamel; Abdelkader Derbali (Cogent Economics & Finance, 2016)
The main purpose of this study is to investigate empirically the impact of energy consumption and economic growth on the environmental degradation as measured by CO2 emissions. We utilize the cointegration test, the fully modified OLS, and the panel causality to examine the causality between environmental pollution and economic aggregates from a panel data of eight Asian countries during the period 1991-2013. We find that the cointegration tests confirm long run relationship among environmental degradation and energy consumption and economic growth along with financial development, trade openness, capital stocks, and urbanization as control variables. In addition, FMOLS results confirm that economic growth and energy consumption have a positive and significant impact on environmental degradation. Besides, panel causality through VECM verifies that bidirectional causal connection is found between energy consumption and economic growth and environmental degradation.
Keywords: C3; F1; G2; O4; Q4; Q5; 330; environmental degradation; economic growth; energy consumption; Asian countries